Potentially toxic elements content in soils in the vicinity of Shamlugh copper mining area (Armenia): ecological, agricultural and health risk assessmen - G. A. Gevorgyan; K. A. Ghazaryan; H. S. Movsesyan (ՀՀ ԳԱԱ հրատ.)
Ecological, agricultural and health risks of the soil pollution by potentially toxic elements (PTEs) (Cu, Pb, As, Ni, Zn, Co) in the vicinity of Shamlugh copper mining area located in the north-east of Armenia were investigated. The results of the study showed that the content of PTEs in the soils sampled in September 2014 may have posed serious risks to soil biological communities, human health as well as agricultural production, in case of soil used for agricultural purpose. Ուսումնասիրվել են Հայաստանի հյուսիս-արևելքում տեղակայված Շամլուղի պղնձարդյունաբերական տարածքի հարակից հողերի պոտենցիալ թունավոր տարրերով (ՊԹՏ) (Cu, Pb, As, Ni, Zn, Co) աղտոտվածության էկոլոգիական, գյուղատնտեսական և առողջական ռիսկերը: Հետազոտության արդյունքները ցույց են տվել, որ 2014 թ. սեպտեմբերին հավաքած հողանմուշներում ՊԹՏ պարունակությունը կարող էր առաջացնել լուրջ ռիսկեր հողի կենսահամակեցությունների, մարդու առողջության, ինչպես նաև գյուղատնտեսական նպատակով հողօգտագործման դեպքում գյուղատնտեսական արտադրության համար:
Keywords: Biology; Ecology